A meta-analysis of aid effectiveness: Revisiting the evidence - Tseday Jemaneh Mekasha; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
As research on the empirical link between aid and growth continues to grow, it is time to revisit the accumulated evidence on aid effectiveness. This paper does this by building on the meta-analysis in our previous work. The availability of more data enables us to conduct a sub-group analysis by disaggregating the sample into different time horizons and assess if there are temporal shifts in aid effectiveness. Our new and updated results show that the previously reported positive evidence of aid's impact is robust to the inclusion of more recent studies in the meta-analysis and this holds for different time horizons as well. The authenticity of the observed effect is also confirmed by results from funnel plots, regression-based tests, and a cumulative meta-analysis for publication bias.
Keywords: F35; O1; O4; 330; aid and growth; meta-analysis; heterogeneity and publication bias